2019
DOI: 10.1029/2019jc015577
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Inundation Mapping From Bitemporal and Dual‐Polarization SAR Imagery Based on Deep Convolutional Neural Networks

Abstract: This study develops an effective and robust method to mine bitemporal and dual-polarization synthetic aperture radar (SAR) imagery information for coastal inundation mapping, based on deep convolutional neural networks. The specially tailored deep convolutional neural network-based SAR coastal flooding mapping network (SARCFMNet) leverages two modifications to improve the accuracy and robustness: the physics-aware input information design and the regularization. The proposed SARCFMNet is applied to the mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…By using observation from satellite and coastal stations simultaneously, GAN can be used to reconstruct the SSH of the whole North-Sea (Zhang, Stanev, et al, 2020). DL also help estimate the iceberg in the pan-Antarctic near-coastal zone that covers the whole Antarctic continent for monitoring ice melt and sea level increasing (Barbat et al, 2019), and coastal inundation for a better understanding of the geospatial and temporal characteristics of coastal flooding (Liu et al, 2019 (Clausen & Nickisch, 2018).…”
Section: Water Resourcesmentioning
confidence: 99%
“…By using observation from satellite and coastal stations simultaneously, GAN can be used to reconstruct the SSH of the whole North-Sea (Zhang, Stanev, et al, 2020). DL also help estimate the iceberg in the pan-Antarctic near-coastal zone that covers the whole Antarctic continent for monitoring ice melt and sea level increasing (Barbat et al, 2019), and coastal inundation for a better understanding of the geospatial and temporal characteristics of coastal flooding (Liu et al, 2019 (Clausen & Nickisch, 2018).…”
Section: Water Resourcesmentioning
confidence: 99%
“…[ 56 ] presented a DCNN-based method that is useful for flooded-building detection in urban areas. Liu et al [ 57 ] proposed an improved DCNN method that has robust performance for coastal-inundation mapping from bi-temporal and dual-polarization SAR images.…”
Section: Application Examplesmentioning
confidence: 99%
“…Krestenitis et al [29] showed that machine learning is an efficient approach to identify an oil spill. Liu et al [30] explored mining SAR imagery for coastal inundation mapping based on deep convolutional neural networks. Machine learning also provides the opportunity for building relationships among multidimensional information.…”
Section: Introductionmentioning
confidence: 99%